Hepatitis B Virus Reactivation After Switch to Cabotegravir/Rilpivirine in Patient with Low Hepatitis B Surface Antibody - Adachi, Eisuke; Sedohara, Ayako; Arizono, Kotaro; Takahashi, Kazuaki; Otani, Amato; Kanno, Yoshiaki; Saito, Makoto; Koga, Michiko; Yotsuyanagi, Hiroshi (Emerging infectious diseases, 2024)
A patient in Japan with HIV began antiretroviral therapy because of acute hepatitis B virus (HBV) 15 years ago, with low hepatitis B surface antibody, and experienced breakthrough HBV reactivation 4 months after switching from bictegravir/emtricitabine/tenofovir alafenamide to cabotegravir/rilpivirine. An immune escape mutation, E164V, was identified in the isolated HBV DNA.